2015
DOI: 10.2903/j.efsa.2015.4115
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on Flavouring Group Evaluation 67 Revision 2 (FGE.67Rev2): Consideration of 28 furan‐substituted compounds evaluated by JECFA at the 55th, 65th and 69th meetings (JECFA, 2001, 2006a, 2009b)

Abstract: The Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) of the European Food Safety Authority was requested to consider evaluations of flavouring substances assessed since 2000 by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), and to decide whether further evaluation is necessary, as laid down in Commission Regulation (EC) No 1565/2000. The substances were evaluated through a stepwise approach (the Procedure) that integrates information on structure-activity relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…For two compounds, trans-hexenal and 2-furylmethylketon, an evaluation was done by EFSA, but no conclusion on the in vivo genotoxic potential of the compounds could be made and therefore further data was requested [40,41]. 2-Furylmethylketon is used as a food flavouring and fragrance and can also be found in tobacco.…”
Section: Flavourings Of Genotoxic Concernmentioning
confidence: 99%
See 1 more Smart Citation
“…For two compounds, trans-hexenal and 2-furylmethylketon, an evaluation was done by EFSA, but no conclusion on the in vivo genotoxic potential of the compounds could be made and therefore further data was requested [40,41]. 2-Furylmethylketon is used as a food flavouring and fragrance and can also be found in tobacco.…”
Section: Flavourings Of Genotoxic Concernmentioning
confidence: 99%
“…The EFSA concluded that the genotoxic potential of furylmethylketon could not be excluded. Based on the available experimental information the substance may give rise to DNA damage, possibly resulting in chromosomal aberrations rather than gene mutations [40]. Trans-hexenal was found in e-liquids with a green fruit flavor.…”
Section: Flavourings Of Genotoxic Concernmentioning
confidence: 99%